1999
DOI: 10.4141/a98-013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of handling, shearing and previous exposure to shearing on cortisol and β-endorphin responses in ewes

Abstract: . 1999. Effects of handling, shearing and previous exposure to shearing on cortisol and β β-endorphin responses in ewes. Can. J. Anim. Sci. 79: [35][36][37][38]. The objectives of the study were to compare the effects of handling and shearing on plasma cortisol and β-endorphin levels of ewes and to determine if adaptation to annual shearing occurred. Plasma cortisol and β-endorphin concentrations were determined during either handling only or handling plus shearing in 12 ewes previously exposed to annual shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…This had been expected and described in other domestic and wild animals (Hargreaves and Hutson 1990a, Mears and others 1999, Bonacic and Macdonald 2003, Carcangiu and others 2008, Piccione and others 2008, 2011, Sanger and others 2011, Casella and other 2016). The clinical parameters and salivary cortisol concentrations in part 1 showed that the stress response was different between restraint methods, although the FCM did not.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This had been expected and described in other domestic and wild animals (Hargreaves and Hutson 1990a, Mears and others 1999, Bonacic and Macdonald 2003, Carcangiu and others 2008, Piccione and others 2008, 2011, Sanger and others 2011, Casella and other 2016). The clinical parameters and salivary cortisol concentrations in part 1 showed that the stress response was different between restraint methods, although the FCM did not.…”
Section: Discussionsupporting
confidence: 76%
“…However, contradictory results have been described in a different study in sheep in which the stress response caused by shearing was even higher in animals which had been previously exposed to shearing (Mears and others 1999). To our best knowledge, such studies have not been performed in alpacas yet.…”
Section: Discussionmentioning
confidence: 94%
“…These events combine to produce an acute stress response: increased plasma concentrations of cortisol, β-endorphin, glucose and increased heart rate and haematocrit (Jephcott et al, 1987;Hargreaves and Hutson, 1990a,b,c;Mears et al, 1999). Shearing produced a larger cortisol response than crutching, isolation and handling (Hargreaves and Hutson, 1990a,c).…”
Section: Introductionmentioning
confidence: 99%
“…Moolchandani et al (2008) examined the effect of restraint and isolation in preand post-applications in sheep and reported that restraint and isolation stress significantly affects on the plasma cortisol with an increasing trend. In another research, Mears et al (1999) examined the effects of handling, shearing and previous exposure to shearing on cortisol and b-endorphin responses in ewes. They found significant differences between pre-and post-applications and indicated that handling and shearing elevated plasma cortisol and b-endorphin concentrations.…”
Section: Stress Responses In Sheepmentioning
confidence: 99%